Performance Optimization of the Intelligence Unit Polres Jepara in the Online Police Record Certificate Service in the Polres Jepara Jurisdiction (Advances in Police Science Research Journal, 2024)
The goal of this research is to optimize the performance of the online police record certificate service of the intelligence unit at Polres Jepara. This research uses SWOT analysis theory and management theory (POAC) as well as concepts contained in laws and regulations governing online police record certificate service procedures.This research is done with a qualitative approach with a type of developmental research, whre data is obtained from interviews, questionnaires and observation report or from literature studies and other reading materials.The writing of this final project was carried out in the jurisdiction of Polres Jepara, which is and Indonesian Police Unit under the jurisdiction of the Java Regional Police. The result of this research found that the implementation of online Police Record Certificate services at Polres Jepara was hampered by the lack of public knowledge about the online system, due the lack of technology that supports the service process either from supporting devices or from signals or networks in accessing the required website.
Keywords: Kata Kunci: Optimalisasi pelayanan, Satuan Intelkam, Surat Keterangan Catatan Kepolisian (SKCK).